An analysis of 342 patients with refractory gastroesophageal reflux disease symptoms using questionnaires, high-resolution manometry, and impedance-pH monitoring. Issue 5 (February 2017) - Wang, Fei; Li, Ping; Ji, Guo-Zhong; Miao, Lin; Fan, Zhining; You, Sihong; Pan, Xueqin; Chen, Xia
Abstract : Abstract: Symptoms of refractory gastroesophageal reflux disease (GERD) are commonly encountered in clinical practice. The aim of this study was to analyze the data obtained from questionnaires, high-resolution manometry (HRM), and ambulatory impedance-pH monitoring in patients with persisting GERD symptoms and to explore the possible underlying causes for this clinical presentation. After completing the questionnaires, the selected patients underwent endoscopy, HRM, and ambulatory impedance-pH monitoring. Based on the results of these investigations, we divided the patients into 4 groups: reflux esophagitis (RE), hypersensitive esophagus (HE), functional heartburn (FH), and nonerosive gastroesophageal reflux disease (NERD). The data from 342 patients were analyzed. One hundred twenty-nine (37.72%) patients experienced refractory GERD symptoms related to acid reflux. The scores on some scales in the Gastrointestinal Symptom Rating Scale (GSRS) questionnaire differed significantly among groups (all P < 0.05). Liquid reflux occurred more frequently in patients with GERD (RE and NERD), while gas reflux was more common in non-GERD patients (FH and HE; all P < 0.05). The RE and NERD groups showed more percent bolus exposure time (BET) when upright (all P < 0.05). Acid exposure time (AET) in the RE and NERD groups was longer than that in the HE and FH groups (all P < 0.05). Fewer than half of the patient symptoms were related to acid reflux. The GSRS questionnaire may be an optimal indicator for patients with refractory GERD symptoms. BET and AET are useful indices to distinguish GERD from other diseases. Gas reflux is probably related to persisting symptoms in FH and HE patients.